Effects of plant extracts on growth, yield and protein content of cowpea (Vigna unguiculata (L.) Walp.) - Lashin, Gamal MA; Azab, Adel A; Hussien, Akram A; Anwar, AM EL (Bangladesh Journal of Botany, 2013)
Aqueous plant extracts of Malva parviflora L. and Artemisia ludia L. were tested in the field on cowpea (Vigna unguiculata (L.) Walp.) plants. The extracts were added alone and in combination. The treatments were applied just one day before irrigation. Data obtained revealed that the growth, yield and protein content of cowpea were stimulated by 10% aqueous extract of M. parviflora and the mixture of 10% Malva with 20% Artemisia. The data also showed that the soil fertility was improved. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15870 Bangladesh J. Bot. 42(1): 99-104, 2013 (June)